2020
DOI: 10.1111/1467-8454.12176
|View full text |Cite
|
Sign up to set email alerts
|

Environmental information disclosure in capital raising

Abstract: In 2010, the Chinese Government issued a policy to require enterprises to disclose environmental information. Using the environmental disclosure information of 204 Chinese listed companies in 20 polluting sectors over the period of 2011–2015, we find that managers tend to withhold environmental information and selectively disguise sensitive environmental information in the face of financial pressure, and where the disclosure of sensitive environmental information would significantly increase the cost of debt f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…It shows that neither the threat of respective regulation (Stanny, 2013) nor actual regulation in place translate into a higher quantity and quality of ER. Vormedal and Ruud (2009) Furthermore, the evidence from Portugal, China and Italy shows that the introduction of ER requirements did not lead to any significant increase in corporate transparency (Ji et al, 2020;Lima Ribeiro & Aibar-Guzmán, 2010;Wang & Bernell, 2013), especially in the provision of hard, objective data (Papa et al, 2022). A similar conclusion may be drawn from the study by Ahmad and Mohamad (2014) i.e.…”
Section: Voluntary Vs Mandatory Ermentioning
confidence: 55%
See 2 more Smart Citations
“…It shows that neither the threat of respective regulation (Stanny, 2013) nor actual regulation in place translate into a higher quantity and quality of ER. Vormedal and Ruud (2009) Furthermore, the evidence from Portugal, China and Italy shows that the introduction of ER requirements did not lead to any significant increase in corporate transparency (Ji et al, 2020;Lima Ribeiro & Aibar-Guzmán, 2010;Wang & Bernell, 2013), especially in the provision of hard, objective data (Papa et al, 2022). A similar conclusion may be drawn from the study by Ahmad and Mohamad (2014) i.e.…”
Section: Voluntary Vs Mandatory Ermentioning
confidence: 55%
“…What is interesting is that the compliance rate after the implementation of the Sarbanes–Oxley Act (SOX) in 2002 is significantly lower than prior to the Act. Furthermore, the evidence from Portugal, China and Italy shows that the introduction of ER requirements did not lead to any significant increase in corporate transparency (Ji et al, 2020; Lima Ribeiro & Aibar‐Guzmán, 2010; Wang & Bernell, 2013), especially in the provision of hard, objective data (Papa et al, 2022). A similar conclusion may be drawn from the study by Ahmad and Mohamad (2014), who find that environmental disclosures of Malaysian public construction companies produced under the stock exchange mandatory reporting regime are incomplete and largely limited to a general narrative and non‐verifiable statements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Does regional heterogeneity affect the explanatory power of the environmental information disclosed by the government and the quality of the ecological environment? Ji (2020) and Peng (2020) found that, in the process of corporate environmental disclosure, managers tend to withhold environmental information and selectively disguise sensitive environmental information [30,31]. Tang (2020) preliminarily discussed the human causes that form the greenwashing of the local government in the stages of collecting, mediating, and disseminating environmental information [32].…”
Section: Introductionmentioning
confidence: 99%
“…While the Chinese government is exploring solutions to incentivize corporations to implement CEID for improved environmental management, this enforcement of environmental regulation is still difficult to achieve due to the low level and quality of CEID in China, which has attracted public criticism [ 7 , 8 , 9 ]. In prior studies, an abundance of evidence has revealed that external public pressure from government regulation and social supervision, such as the implementation of measures for the disclosure of environmental information and government financing requirements, is an important force in driving CEID [ 10 , 11 , 12 , 13 ]. Current domestic regulators do not yet have standardized disclosure requirements for corporate environmental information [ 7 , 14 ], which suggests that inadequate access to environmental information is the main reason for China’s weak environmental management [ 15 ].…”
Section: Introductionmentioning
confidence: 99%